Tetrahydrocurcumin Downregulates MAPKs/cPLA2 Signaling and Attenuates Platelet Thromboxane A2 Generation, Granule Secretion, and Thrombus Growth - Li, Weiqi; Ma, Yongjie; Zhang, Chunmei; Chen, Binlin; Zhang, Xiandan; Yu, Xin; Shuai, Hongyan; He, Qilian; Ya, Fuli (Thrombosis and Haemostasis, 2021)
Platelet granule secretion plays a key role in atherothrombosis. Curcumin, a natural polyphenol compound derived from turmeric, exerts multiple biological activities. The current study sought to investigate the efficacy of tetrahydrocurcumin (THC, the major active metabolite of curcumin) on platelet granule secretion in vitro and thrombus formation in vivo. We found that THC significantly attenuated agonist-induced granule secretion in human gel-filtered platelets in vitro, including CD62P and CD63 expression and platelet factor 4, CCL5, and adenosine triphosphate release. These inhibitory effects of THC were partially mediated by the attenuation of cytosolic phospholipase A2 (cPLA2) phosphorylation, leading to a decrease in thromboxane A2 (TxA2) generation. Moreover, the MAPK (Erk1/2, JNK1/2, and p38 MAPK) signaling pathways were downregulated by THC treatment, resulting in reduced cPLA2 activation, TxA2 generation, and granule secretion. Additionally, THC and curcumin attenuated murine thrombus growth in a FeCl3-induced mesenteric arteriole thrombosis model in C57BL/6J mice without prolonging the tail bleeding time. THC exerted more potent inhibitory effects on thrombosis formation than curcumin. Through blocking cyclooxygenase-1 activity and thus inhibiting platelet TxA2 synthesis and granule secretion with aspirin, we found that THC did not further decrease the inhibitory effects of aspirin on thrombosis formation. Thus, through inhibiting MAPKs/cPLA2 signaling, and attenuating platelet TxA2 generation, granule secretion, and thrombus formation, THC may be a potent cardioprotective agent.
Keywords: tetrahydrocurcumin; platelet granule; cytosolic phospholipase A2; thromboxane A2; thrombosis